Landfill Gas Monitoring At Borehole Wells Using An Autonomous Environmental Monitoring System - Kiernan, Breda M.; Beirne, Stephen; Fay, Cormac; Diamond, Dermot (Zenodo, 2008)
An autonomous environmental monitoring system (Smart Landfill) has been constructed for the quantitative measurement of the components of landfill gas found at borehole wells at the perimeter of landfill sites. The main components of landfill gas are the greenhouse gases, methane and carbon dioxide and have been monitored in the range 0-5 % volume. This monitoring system has not only been tested in the laboratory but has been deployed in multiple field trials and the data collected successfully compared with on-site monitors. This success shows the potential of this system for application in environments where reliable gas monitoring is crucial. : {"references": ["US Environmental Protection Agency (2002)\n\"Greenhouse Gases and Global Warming Potential\nValues\"", "Spokas, K., J. Bogner, et al. (2006) \"Methane mass\nbalance at three landfill sites: What is the efficiency of\ncapture by gas collection systems?\" Waste Management\n26(5): 516-525", "Environment Agency, UK \"Guidance on monitoring\nlandfill gas surface emissions\"", "Aitchison, E. \"Methane generation from UK landfill sites\nand its use as an energy resource\" Energy Conversion\nand Management 1996, 37(6-8), 1111-1116", "Diot, M., Y. M. le Golvan, et al. (2000) \"Landfill Biogas\nEmissions Measurements: Qualification and\nQuantification of the Pathways of Emitted Methane\"\nIntercontinental Landfill Research Symposium, Lulea,\nSweden.", "Czepiel, P. M., J. H. Shorter, et al. (2003) \"The influence\nof atmospheric pressure on landfill methane emissions\"\nWaste Management 23(7): 593-598", "Young, A. (1992) \"The Effects of Fluctuations in\nAtmospheric Pressure on Landfill Gas Migration and\nComposition\" Water, Air and Soil Pollution 64: 601-616", "Christophersen, M. and P. Kjeldsen (2002) \"Factors\nGoverning Lateral Gas Migration and Subsequent\nEmission in Soil Adjacent to an Old Landfill\"\nIntercontinental Landfill Research Symposium, Lulea\nUniversity of Technology, Lulea, Sweden", "Maurice, C. and A. Lagerkvist (2000) \"LFG emission\nmeasurements in arctic climate conditions\"\nIntercontinental Landfill Research Symposium, Lulea,\nSweden.\n[10] Environment Agency, UK (2002) \"Guidance on Landfill\nGas Flaring\"\n[11] McGettigan, M., C. O'Donnell, et al. (2000) \"National\nAir Quality Monitoring Programme\" Environmental\nProtection Agency, Ireland\n[12] Crowley, K., Frisby, J., Murphy, S., Roantree, M. and D.\nDiamond (2005) \"Web-based real-time temperature\nmonitoring of shellfish catches using a wireless sensor\nnetwork\" Sensors and Actuators A 122: 222-230\n[13] Frisby, J., Raftery, D., Kerry, J.P. and D. Diamond\n(2005) \"Development of an autonomous, wireless pH and\ntemperature sensing system for monitoring pig meat\nquality\" Meat Science 70: 329-336\n[14] Sequeira, M., Bowden, M., Minogue, E. and D. Diamond\n(2002) \"Towards autonomous environmental monitoring\nsystems\" Talanta 56: 355-363\n[15] McGraw, C. M., Stitzel, S. E., Cleary, J., Slater, C. and\nD. Diamond (2007) \"Autonomous microfluidic system\nfor phosphate detection\" Talanta 71: 1180-1185\n[16] IRgaskIT Carbon Dioxide Monitor Operating Manual\nV1.2 supplied by Edinburgh Instruments Limited 2006"]}